Penggunaan Istagram Sebagai Media Interaksi Sosial Pada Mahasiswa Pendidikan Sosiologi 2019 Universitas Sultan Ageng Tirtayasa: (Studi Kasus Ragam Sosial Budaya Perspektif dan Konteks Psikologi Sosial) - Isni Reniati; Rini Agustin; Chorunnisa Chorunnisa; Danik Suryani; Ria Risdiana; Opy Trisnawati; Wahid Abdul Kudus (Journal Pendidikan Ilmu Pengetahuan Sosial, 2022)
The purpose of this study is to find out the use of Instagram as a medium for social interaction among 2019 Sociology Education Students at Sultan Ageng Tirtayasa University (Case study of various socio-cultural perspectives and social psychology contexts). In fulfilling information data, the authors used three data collection techniques, namely by observation, interviews and supplemented by documentation from journals, books, articles, and other sources. Through interviews, the researcher selected six main informants to answer questions that had been determined based on theory and one key informant who became the all-knowing center among the six main informants. The data found is then analyzed, according to Miles & Huberman (1992: 16) data analysis consists of several stages, namely, (1) data collection, (2) data reduction), (3) data presentation, (4) drawing conclusions, and (5) evaluation. To facilitate researchers in carrying out research activities, researchers use a series of working hypotheses or a reference sentence used in interviews and guidelines for compiling research results and discussion. The hypotheses used are (1) Instagram is a medium of social interaction that is of interest to the current generation, (2) Instagram is an example of cultural and social diversity in society, and (3) Instagram has both positive and negative impacts on users. Which will be examined using the theory of Symbolic Interactionism. The hypotheses used are (1) Instagram is a medium of social interaction that is of interest to the current generation, (2) Instagram is an example of cultural and social diversity in society, and (3) Instagram has both positive and negative impacts on users. Which will be examined using the theory of Symbolic Interactionism. The hypotheses used are (1) Instagram is a medium of social interaction that is of interest to the current generation, (2) Instagram is an example of cultural and social diversity in society, and (3) Instagram has both positive and negative impacts on users. Which will be examined using the theory of Symbolic Interactionism.